SPORT PARTICIPATION IN SCHOOLS: A BIBLIOMETRIC STUDY OF TRENDS AND RESEARCH FOCUS - Haniyyah, Salma; Fitri, Mustika; Paramitha, Sandey Tantra; Apriady, Hilmy (STKIP Singkawang, 2024)
Research on sport participation in schools has undergone dynamic development. This study explores the trends and advancements in student sport participation using a bibliometric analysis approach. A total of 2,342 articles published between 2014 and 2024 were analyzed to uncover the evolution, focus areas, and key contributions within this field. Drawing on data from the Scopus database, the bibliometric analysis investigates scientific publications related to sport participation in educational contexts. The use of VOSviewer software enabled the visualization of collaboration networks among researchers, institutions, and research topics, offering deeper insights into the structure and dynamics of the research landscape. This method provides an overview of trends over time, identifies prominent themes, and highlights the contributions of leading institutions and scholars. The study emphasizes the significance of continuous research and collaborative efforts in advancing sport participation in schools. Furthermore, a systematic literature review was conducted to identify potential research directions, offering comprehensive guidance for future studies in the field.